A sodium ion precursor material and its preparation method and application
By precipitating doped boron and potassium in the precursor material of the sodium ion battery positive electrode material, the problem of insufficient structural deformation and cycle stability of the sodium ion battery positive electrode material during the deintercalation process is solved, and the structural stability and cycle performance of the material are improved.
Patent Information
- Application Number
- CN202310254255.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The existing sodium ion battery positive electrode materials are prone to phase change during the deintercalation process, resulting in structural deformation, insufficient cyclic stability and specific capacity, and the existing doping technology is not conducive to industrial expansion of production.
Boron (B) and potassium (K) are added simultaneously during the preparation of sodium ion precursor material by co-precipitation method, so that the B and K elements in the sodium ion layered oxide positive electrode material are uniformly distributed, stabilizing the structure and improving cycling performance.
The structural stability and cyclic performance of sodium ion positive electrode materials have been improved, the specific capacity is improved and the capacity retention rate is maintained, which is suitable for large-scale production.
Smart Images

Figure BDA0004128968020000101 
Figure BDA0004128968020000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries and relates to a sodium ion precursor material and a preparation method and application thereof. Background Art
[0002] At present, with the emergence of portable wearable devices, electric vehicles and smart grids, the demand for lithium is increasing, and the world's lithium resource reserves have quickly entered a situation of supply exceeding demand. At the same time, due to the limitations of production processes and expansion cycles, the cost of battery-grade lithium carbonate and high-purity lithium carbonate with higher technical content has risen sharply, and the recent price has exceeded 600,000 yuan per ton. The contradiction between the explosive demand for lithium batteries and the mismatch of lithium resources is bound to intensify, and the development of sodium-ion batteries is a good direction.
[0003] In recent years, transition metal layered oxides Na x TmO2 (Tm is a transition element) has the advantages of high specific capacity, simple preparation method, reversible deintercalation, etc., making transition metal layered oxides very promising candidate materials for the positive electrode of sodium ion batteries. Therefore, there is currently extensive research on it in related fields. For example, CN108565457A provides a sodium ion battery positive electrode material, a preparation method thereof, and a sodium ion battery. The chemical formula of the sodium ion battery positive electrode material provided by the present invention is Na x Ni 0.167 Co 0.167 Mn 0.67 O2, wherein 0.5≤x≤0.8, the shape of the sodium ion battery positive electrode material is spherical, and the concentrations of manganese and nickel are distributed in a gradient along the radial direction.
[0004] However, there are still some problems with transition metal layered oxides. For example, phase changes are prone to occur during the embedding and de-embedding process, leading to structural deformation, which in turn causes structural degradation. The reversible capacity decays severely during the cycle and the cycle stability is poor.
[0005] And because sodium ions have a larger radius, not only do they require higher energy to drive their movement, but they are also prone to destroying the positive electrode structure during the deintercalation process. Therefore, they are usually doped to obtain higher specific capacity and better cycle performance. However, existing doping technologies are mostly solid-phase methods, sol-gel methods or solvent evaporation methods, which are not conducive to industrial expansion of production.
[0006] For example, CN109962215A discloses a doped modified P2 type sodium ion type sodium ion battery positive electrode material. Its characteristics are: the doped modified P2 type sodium ion type sodium ion battery positive electrode material is a doped structure Na 0.67 Mn x Fe 1-x O2 positive electrode material, cation doped material Na 0.67 Mn0.6 Fe 0.4-x-y A x B y O2, 0<x≤0.1, 0<y≤0.1, the doped cations include two parts: A is the metal cation participating in the redox reaction during the charge and discharge process, and B is the inert metal cation during the charge and discharge process. The preparation method used in this document is a solid phase method.
[0007] Therefore, how to obtain a uniform distribution of doping elements and stabilize the structure of the sodium ion oxide positive electrode material to improve its electrochemical performance is a technical problem that needs to be solved urgently. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a sodium ion precursor material and a preparation method and application thereof. The present invention simultaneously incorporates B and K in the preparation process of the sodium ion precursor material by a coprecipitation method, so that the B and K elements in the obtained sodium ion layered oxide positive electrode material are evenly distributed, the structural stability of the sodium ion layered oxide positive electrode material is stabilized, and the positive electrode release capacity of the sodium ion layered oxide positive electrode material is more favorable, and the cycle performance of the sodium ion layered oxide positive electrode material is improved.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a sodium ion precursor material, wherein the sodium ion precursor material comprises a nickel-iron-manganese hydroxide material; the nickel-iron-manganese hydroxide material is doped with boron and potassium.
[0011] In the sodium ion precursor material provided by the present invention, B and K are simultaneously doped during the preparation process of the sodium ion precursor material, so that the B and K elements are uniformly distributed in the obtained sodium ion layered oxide positive electrode material, and B doping can improve the structural stability of the sodium ion layered oxide positive electrode material and improve the cycle performance of the positive electrode material, while K ions can stabilize the structure of the sodium ion layered oxide positive electrode material, which is more conducive to the deintercalation of sodium ions in the layered oxide positive electrode material; in the present invention, B and K doping work synergistically to achieve both improved specific capacity and improved cycle performance, while if only B is doped, the purpose of improving specific capacity cannot be achieved, and if only K is doped, the doping amount cannot be accurately controlled; and if B and K are not doped in the precursor stage, it will be unfavorable for the uniform distribution of the elements.
[0012] Preferably, the chemical formula of the sodium ion precursor material is: 24 H 20 BK-Ni x Fe y Mn (1-x-y)(OH)2, wherein 0.01≤z≤0.05, 0.1≤x≤0.34, 0.1≤y≤0.34.
[0013] For example, the z can be 0.01, 0.013, 0.015, 0.018, 0.02, 0.023, 0.025, 0.028, 0.03, 0.033, 0.035, 0.038, 0.4, 0.043, 0.045 or 0.05, etc.; the x can be 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3, 0.32 or 0.34, etc., and the y can be 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3, 0.32 or 0.34, etc.
[0014] In the sodium ion precursor material provided by the present invention, if the z value is too small, that is, too little B and K are doped, it is not conducive to improving the performance of the sodium ion positive electrode, while if the z value is too large, that is, too much B and K are doped, it will lead to a decrease in specific capacity.
[0015] In a second aspect, the present invention further provides a method for preparing the sodium ion precursor material as described in the first aspect, the preparation method comprising the following steps:
[0016] A nickel-iron-manganese-boron mixed salt solution, a potassium source solution and a precipitant solution are added to the bottom liquid in parallel to carry out a co-precipitation reaction, so as to obtain the sodium ion precursor material.
[0017] The preparation method provided by the present invention performs doping of B and K by a coprecipitation method so that the doping elements are evenly distributed. During the preparation process, if the boron source is added alone (not as one of the mixed salts), it is not conducive to the uniform distribution of the elements. If the potassium source is not added alone, it will cause it to directly participate in the reaction. That is, in the present invention, the boron source needs to be added together (as a mixed salt), and the potassium source needs to be added alone. Only in this way can a precursor material with uniform distribution of B and K be obtained. Moreover, it is easy to control, the preparation method is simple, and it is suitable for large-scale production.
[0018] Preferably, the preparation of the nickel-iron-manganese-boron mixed salt solution comprises:
[0019] A nickel source, an iron source and a manganese source are prepared to obtain a ternary mixed solution, and then a boron source is added and mixed to obtain a nickel-iron-manganese-boron mixed salt solution.
[0020] Preferably, the molar concentration of the ternary mixed solution is 2-4 mol / L, for example, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L or 4 mol / L.
[0021] Preferably, the molar concentration of boron in the nickel-iron-manganese-boron mixed salt solution is 0.15-0.8 mol / L, for example, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L, 0.65 mol / L, 0.7 mol / L, 0.75 mol / L or 0.8 mol / L, etc.
[0022] In the present invention, if the molar concentration of boron in the nickel-iron-manganese-boron mixed salt solution is too high, it will affect the electrochemical properties of the subsequent positive electrode material, while if it is too low, it will lead to poor doping effect.
[0023] Preferably, the nickel source includes any one of nickel nitrate, nickel sulfate or nickel chloride, or a combination of at least two of them.
[0024] Preferably, the iron source comprises ferrous sulfate.
[0025] Preferably, the manganese source includes any one of manganese nitrate, manganese sulfate or manganese chloride, or a combination of at least two of them.
[0026] Preferably, the boron source comprises sodium tetraphenylborate.
[0027] In the present invention, sodium tetraphenylborate is selected as the boron source, which can better achieve the co-doping of B and K elements. If other boron sources, such as H3BO3, are selected, K will not be precipitated.
[0028] Preferably, the potassium source comprises potassium oxalate.
[0029] In the present invention, potassium oxalate is used as a potassium source, which can not only provide K ions but also act as a complexing agent in the system, while other potassium salts, such as K2SO4, require the addition of a complexing agent solution, which complicates the process.
[0030] Preferably, the molar concentration of the potassium source solution is 0.1-2.4 mol / L, for example, 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L or 2.4 mol / L.
[0031] Preferably, the molar concentration of the precipitant solution is 1 to 12 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L or 12 mol / L.
[0032] Preferably, the pH value during the coprecipitation reaction is 9 to 11.8, for example, 9, 9.3, 9.5, 9.8, 10, 10.3, 10.5, 10.8, 11, 11.3, 11.5 or 11.8.
[0033] Preferably, the reaction temperature during the coprecipitation reaction is 40-60°C, such as 40°C, 45°C, 50°C, 55°C or 60°C.
[0034] Preferably, the reaction time in the coprecipitation reaction process is 50 to 100 h, for example, 50 h, 55 h, 60 h, 65 h, 70 h, 75 h, 80 h, 85 h, 90 h, 95 h or 100 h.
[0035] Preferably, the stirring rate during the coprecipitation reaction is 200-400 r / min, for example, 200 r / min, 230 r / min, 250 r / min, 280 r / min, 300 r / min, 330 r / min, 350 r / min, 380 r / min or 400 r / min.
[0036] In the present invention, uniform doping of B and K in the precursor stage is achieved by coordinating parameters (pH, temperature, time and stirring rate) during the coprecipitation process.
[0037] As a preferred technical solution, the preparation method comprises the following steps:
[0038] A nickel source, an iron source and a manganese source are prepared to obtain a ternary mixed solution with a molar concentration of 2 to 4 mol / L, and then a boron source is added and mixed to obtain a nickel-iron-manganese-boron mixed salt solution with a boron molar concentration of 0.15 to 0.8 mol / L;
[0039] A nickel-iron-manganese-boron mixed salt solution, a potassium source solution and a precipitant solution are added to the bottom liquid in parallel, the pH value is maintained at 9-11.8, and a coprecipitation reaction is carried out at 40-60° C. and a stirring rate of 200-400 r / min for 50-100 hours to obtain the sodium ion precursor material.
[0040] In a third aspect, the present invention provides a sodium ion positive electrode material, which is obtained by mixing and sintering the sodium ion precursor material as described in the first aspect and a sodium source.
[0041] The sodium ion positive electrode material provided by the present invention realizes the doping of B and K in the precursor stage, and further undergoes sintering to obtain a positive electrode material with a stable structure and excellent performance.
[0042] Preferably, the chemical formula of the sodium ion positive electrode material is Na 0.67-z K z Bz Ni x Fe y Mn (1-x-y) O2, where 0.01≤z≤0.05, 0.1≤x≤0.34, 0.1≤y≤0.34.
[0043] For example, the z can be 0.01, 0.013, 0.015, 0.018, 0.02, 0.023, 0.025, 0.028, 0.03, 0.033, 0.035, 0.038, 0.4, 0.043, 0.045 or 0.05, etc.; the x can be 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3, 0.32 or 0.34, etc., and the y can be 0.1, 0.13, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3, 0.32 or 0.34, etc.
[0044] Preferably, the sodium source comprises sodium carbonate.
[0045] Preferably, the sintering includes primary sintering and secondary sintering.
[0046] Preferably, the primary sintering temperature is 300-500°C, for example, 300°C, 350°C, 400°C, 450°C or 500°C.
[0047] Preferably, the primary sintering time is 3 to 6 hours, such as 3 hours, 4 hours, 5 hours or 6 hours.
[0048] Preferably, the secondary sintering temperature is 700-900°C, for example, 700°C, 750°C, 800°C, 850°C or 900°C.
[0049] Preferably, the secondary sintering time is 12 to 24 hours, for example, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours or 24 hours.
[0050] In a fourth aspect, the present invention further provides a sodium ion battery, comprising the sodium ion positive electrode material as described in the third aspect.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] (1) In the sodium ion precursor material provided by the present invention, B and K are simultaneously doped during the preparation process of the sodium ion precursor material, so that the B and K elements are evenly distributed in the obtained sodium ion layered oxide positive electrode material, and B doping can improve the structural stability of the sodium ion layered oxide positive electrode material and improve the cycle performance of the positive electrode material, while K ions can stabilize the structure of the sodium ion layered oxide positive electrode material. B and K work synergistically to improve the capacity and cycle performance of the sodium ion positive electrode material. The positive electrode in the sodium ion battery is prepared from the sodium ion precursor provided by the present invention, and in the precursor, when 0.01≤z≤0.05, at a voltage of 2 to 4V, the initial specific capacity of the battery at 0.1C can reach 170.85mAh·g -1 The capacity retention rate after 100 cycles can reach more than 90.8%.
[0053] (2) The preparation method provided by the present invention performs B and K doping by co-precipitation method. Boron sources are added together (as a mixed salt), while potassium sources are added separately, so that the doping elements are evenly distributed, thereby obtaining a sodium ion precursor material with a stable structure, which is easy to control, has a simple preparation method, and is suitable for large-scale production. DETAILED DESCRIPTION
[0054] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0055] Example 1
[0056] This embodiment provides a sodium ion precursor material, the chemical formula of which is 0.01C 24 H 20 BK-Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2.
[0057] The preparation method of the sodium ion precursor material is as follows:
[0058] Nickel sulfate, ferrous sulfate and manganese sulfate were weighed according to the stoichiometric ratio of Ni:Fe:Mn=1:1:1 to prepare a ternary solution of 2 mol / L, and then sodium tetraphenylborate was added thereto and stirred to dissolve, so that the concentration of B was 0.5 mol / L; a bottom liquid was added to the reactor (water was added to 1 / 3 of the reactor, oxalic acid was added to make the oxalate concentration 1-7 g / L, and liquid alkali was added to control the pH at 11-12), N2 was introduced, the temperature was raised to 50°C, the quaternary solution, 2 mol / L sodium hydroxide solution and 0.1 mol / L potassium oxalate solution were added to the reactor in parallel and stirred continuously, the stirring speed was 360 r / min, the pH of the reaction system was maintained at 10, and the reaction was carried out for 80 hours to obtain a 0.01C 24 H 20 BK-Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 A spherical five-membered precursor of (OH)2.
[0059] Example 2
[0060] This embodiment provides a sodium ion precursor material, the chemical formula of which is 0.03C 24 H 20 BK-Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2.
[0061] The preparation method of the sodium ion precursor material is as follows:
[0062] Nickel sulfate, ferrous sulfate and manganese sulfate were weighed according to the stoichiometric ratio of Ni:Fe:Mn=1:1:1 to prepare a ternary solution of 3 mol / L, and then sodium tetraphenylborate was added thereto and stirred to dissolve, so that the concentration of B was 0.5 mol / L; a bottom liquid was added to the reactor (water was added to 1 / 3 of the reactor, oxalic acid was added to make the oxalate concentration 1-7 g / L, and liquid alkali was added to control the pH at 11-12), N2 was introduced, the temperature was raised to 40°C, the quaternary solution, 5 mol / L sodium hydroxide solution and 1 mol / L potassium oxalate solution were added to the reactor in parallel and stirred continuously, the stirring speed was 200 r / min, the pH of the reaction system was maintained at 11, and the reaction was carried out for 100 hours to obtain a 0.03C 24 H 20 BK-Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 A spherical five-membered precursor of (OH)2.
[0063] Example 3
[0064] This embodiment provides a sodium ion precursor material, the chemical formula of which is 0.05C24 H 20 BK-Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2.
[0065] The preparation method of the sodium ion precursor material is as follows:
[0066] Nickel sulfate, ferrous sulfate and manganese sulfate were weighed according to the stoichiometric ratio of Ni:Fe:Mn=1:1:1 to prepare a ternary solution of 4 mol / L, and then sodium tetraphenylborate was added thereto and stirred to dissolve, so that the concentration of B was 0.8 mol / L; a bottom liquid was added to the reactor (water was added to 1 / 3 of the reactor, oxalic acid was added to make the oxalate concentration 1-7 g / L, and liquid alkali was added to control the pH at 11-12), N2 was introduced, the temperature was raised to 60°C, the quaternary solution, 12 mol / L sodium hydroxide solution and 2 mol / L potassium oxalate solution were added to the reactor in parallel and stirred continuously, the stirring speed was 400 r / min, the pH of the reaction system was maintained at 9, and the reaction was carried out for 50 hours to obtain a structural formula of 0.05C 24 H 20 BK-Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 A spherical five-membered precursor of (OH)2.
[0067] Example 4
[0068] The difference between this embodiment and embodiment 1 is that the chemical formula of the sodium ion precursor material in this embodiment is 0.01C 24 H 20 BK-Ni 0.2 Fe 0.2 Mn 0.6 (OH)2.
[0069] The rest of the preparation methods and parameters were the same as those in Example 1.
[0070] Example 5
[0071] The difference between this embodiment and embodiment 1 is that the chemical formula of the sodium ion precursor material in this embodiment is 0.01C 24 H 20 BK-Ni 0.1 Fe 0.1 Mn 0.8 (OH)2.
[0072] The rest of the preparation methods and parameters were the same as those in Example 1.
[0073] Example 6
[0074] The difference between this embodiment and embodiment 1 is that the chemical formula of the sodium ion precursor material in this embodiment is 0.06C 24 H 20 BK-Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2.
[0075] The rest of the preparation methods and parameters were the same as those in Example 1.
[0076] Example 7
[0077] The difference between this embodiment and embodiment 1 is that the chemical formula of the sodium ion precursor material in this embodiment is 0.005C 24 H 20 BK-Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2.
[0078] The rest of the preparation methods and parameters were the same as those in Example 1.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that in this comparative example, only boron is doped without potassium, and potassium oxalate is not added during the preparation process, but sodium oxalate is used.
[0081] The rest of the preparation methods and parameters were the same as those in Example 1.
[0082] Comparative Example 2
[0083] The difference between this comparative example and Example 1 is that in this comparative example, only potassium is doped without boron, and sodium tetraphenylborate is not added during the preparation process.
[0084] The rest of the preparation methods and parameters were the same as those in Example 1.
[0085] Comparative Example 3
[0086] The difference between this comparative example and Example 1 is that in this comparative example, the boron source is added separately, that is, the nickel-iron-manganese ternary mixed salt solution, sodium tetraphenylborate solution, potassium oxalate solution and sodium hydroxide solution are added to the base liquid in parallel.
[0087] The rest of the preparation methods and parameters were the same as those in Example 1.
[0088] The sodium ion precursor material provided by Example 1-7 and Comparative Example 1-3 was mixed with sodium carbonate at a molar ratio of 1:0.7 (ratio to sodium element), sintered at 400°C for 5 hours, and then heated to 800°C for a second sintering for 18 hours to obtain a sodium ion positive electrode material, whose specific chemical formula is shown in Table 1.
[0089] The sodium ion positive electrode materials provided in Examples 1-7 and Comparative Examples 1-3 are used to prepare positive electrode sheets, and then to prepare sodium ion batteries.
[0090] The sodium ion batteries provided in Examples 1-7 and Comparative Examples 1-3 were subjected to performance tests at a test voltage range of 2.0-4.0 V and a current density of 0.1 C. The test results are shown in Table 1.
[0091] Table 1
[0092]
[0093]
[0094] From the data results of Examples 1, 6 and 7, it can be seen that in the sodium ion precursor material, if the z value is too large, the doping element will occupy too much Na site, which will reduce the material specific capacity. If the z value is too small, it will not be conducive to improving the material performance.
[0095] From the data results of Example 1 and Comparative Examples 1-2, it can be seen that in the present invention, the synergistic effect of B and K doping can achieve both improved specific capacity and improved cycle performance; simple doping with B can only improve the cycle performance of the material; and simple doping with K cannot precipitate the K element, and only a small amount of adsorbed K element can be obtained in the material, which cannot be accurately quantified, and the distribution range of the K element in the material cannot be controlled.
[0096] From the data results of Example 1 and Comparative Example 3, it can be seen that in the preparation method provided by the present invention, the boron source must be added together with the nickel-iron-manganese ternary mixed salt solution as a mixed salt, otherwise the doping elements will be unevenly distributed, affecting the doping effect.
[0097] In summary, the coprecipitation method is used to dope B and K. The boron source should be added together (as a mixed salt), while the potassium source should be added separately to make the doping elements evenly distributed, so that the B and K elements in the obtained sodium ion layered oxide positive electrode material are evenly distributed, and B doping can improve the structural stability of the sodium ion layered oxide positive electrode material and improve the cycle performance of the positive electrode material, while K ions can stabilize the structure of the sodium ion layered oxide positive electrode material. B and K work synergistically to improve the capacity and cycle performance of the sodium ion positive electrode material. The positive electrode in the sodium ion battery is prepared from the sodium ion precursor provided by the present invention, and in the precursor, when 0.01≤z≤0.05, the initial specific capacity of the battery at 0.1C can reach 170.85mAh·g at a voltage of 2 to 4V. -1 The capacity retention rate after 100 cycles can reach more than 90.8%.
[0098] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium ion precursor material, characterized in that: The sodium ion precursor material includes nickel iron manganese hydroxide material; The nickel-iron-manganese hydroxide material is doped with boron and potassium; The sodium ion precursor material is prepared by the following method, which comprises the following steps: preparing a nickel source, an iron source and a manganese source to obtain a ternary mixed solution, and then adding a boron source to mix, to obtain a nickel-iron-manganese-boron mixed salt solution; adding the nickel-iron-manganese-boron mixed salt solution, a potassium source solution and a precipitant solution to a bottom liquid in parallel for a co-precipitation reaction, to obtain the sodium ion precursor material; The boron source includes sodium tetraphenylborate; the potassium source includes potassium oxalate; The general chemical formula of the sodium ion precursor material is zC 24 H 20 BK-Ni x Fe y Mn (1-x-y) (OH)2, wherein 0.01≤z≤0.05, 0.1≤x≤0.34, 0.1≤y≤0.
34.
2. A method for preparing a sodium ion precursor material according to claim 1, characterized in that: The preparation method comprises the following steps: A nickel source, an iron source and a manganese source are prepared to obtain a ternary mixed solution, and then a boron source is added to the mixture to obtain a nickel-iron-manganese-boron mixed salt solution; the nickel-iron-manganese-boron mixed salt solution, a potassium source solution and a precipitant solution are added to the bottom liquid in parallel to perform a co-precipitation reaction to obtain the sodium ion precursor material; The boron source includes sodium tetraphenylborate; and the potassium source includes potassium oxalate.
3. The method for preparing the sodium ion precursor material according to claim 2, characterized in that: The molar concentration of the ternary mixed solution is 2-4 mol / L.
4. The method for preparing the sodium ion precursor material according to claim 2, characterized in that: The molar concentration of boron in the nickel-iron-manganese-boron mixed salt solution is 0.15-0.8 mol / L.
5. The method for preparing the sodium ion precursor material according to claim 2, characterized in that: The nickel source includes any one of nickel nitrate, nickel sulfate or nickel chloride, or a combination of at least two of them.
6. The method for preparing the sodium ion precursor material according to claim 2, characterized in that: The iron source includes ferrous sulfate.
7. The method for preparing a sodium ion precursor material according to claim 2, characterized in that: The manganese source includes any one of manganese nitrate, manganese sulfate or manganese chloride, or a combination of at least two of them.
8. The method for preparing a sodium ion precursor material according to claim 2, characterized in that: The molar concentration of the potassium source solution is 0.1-2.4 mol / L.
9. The method for preparing a sodium ion precursor material according to claim 2, characterized in that: The molar concentration of the precipitant solution is 1-12 mol / L.
10. The method for preparing a sodium ion precursor material according to claim 2, characterized in that: The pH value during the coprecipitation reaction is 9-11.
8.
11. The method for preparing a sodium ion precursor material according to claim 2, characterized in that: The reaction temperature during the coprecipitation reaction is 40-60°C.
12. The method for preparing a sodium ion precursor material according to claim 2, characterized in that: The reaction time during the coprecipitation reaction is 50 to 100 hours.
13. The method for preparing a sodium ion precursor material according to claim 2, characterized in that: The stirring rate during the coprecipitation reaction is 200-400 r / min.
14. The method for preparing a sodium ion precursor material according to claim 2, characterized in that: The preparation method comprises the following steps: A nickel source, an iron source and a manganese source are prepared to obtain a ternary mixed solution with a molar concentration of 2 to 4 mol / L, and then a boron source is added and mixed to obtain a nickel-iron-manganese-boron mixed salt solution with a boron molar concentration of 0.15 to 0.8 mol / L; A nickel-iron-manganese-boron mixed salt solution, a potassium source solution and a precipitant solution are added to the bottom liquid in parallel, the pH value is maintained at 9-11.8, and a coprecipitation reaction is carried out at 40-60° C. and a stirring rate of 200-400 r / min for 50-100 hours to obtain the sodium ion precursor material.
15. A sodium ion positive electrode material, characterized in that: The sodium ion positive electrode material is obtained by mixing and sintering the sodium ion precursor material as claimed in claim 1 and a sodium source.
16. The sodium ion positive electrode material according to claim 15, characterized in that The chemical formula of the sodium ion positive electrode material is Na 0.67-z K z B z Ni x Fe y Mn (1-x-y) O2, where 0.01≤z≤0.05, 0.1≤x≤0.34, 0.1≤y≤0.
34.
17. The sodium ion positive electrode material according to claim 15, characterized in that The sodium source includes sodium carbonate.
18. The sodium ion positive electrode material according to claim 15, characterized in that The sintering includes primary sintering and secondary sintering.
19. The sodium ion positive electrode material according to claim 18, characterized in that The primary sintering temperature is 300-500°C.
20. The sodium ion positive electrode material according to claim 18, characterized in that The time of the primary sintering is 3 to 6 hours.
21. The sodium ion positive electrode material according to claim 18, characterized in that The secondary sintering temperature is 700-900°C.
22. The sodium ion positive electrode material according to claim 18, characterized in that The secondary sintering time is 12 to 24 hours.
23. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion positive electrode material according to any one of claims 15 to 22.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN108565457A
Doped modified P2 sodium ion type sodium ion battery positive electrode material
CN109962215A
Zirconium-aluminum double-doped nickel-cobalt-manganese hydroxide as well as preparation method and application thereof
CN115321610A
Boron-doped sodium-ion cathode material, method of producing same and its use
EP3415470A1